Adolescent search roles. Issue 1 (5th December 2012) - Foss, Elizabeth; Druin, Allison; Yip, Jason; Ford, Whitney; Golub, Evan; Hutchinson, Hilary
<x xml:space="preserve">Abstract</x> In this article, we present an in‐home observation and in‐context research study investigating how 38 adolescents aged 14–17 search on the Internet. We present the search trends adolescents display and develop a framework of search roles that these trends help define. We compare these trends and roles to similar trends and roles found in prior work with children ages 7, 9, and 11. We use these comparisons to make recommendations to adult stakeholders such as researchers, designers, and information literacy educators about the best ways to design search tools for children and adolescents, as well as how to use the framework of searching roles to find better methods of educating youth searchers. Major findings include the seven roles of adolescent searchers, and evidence that adolescents are social in their computer use, have a greater knowledge of sources than younger children, and that adolescents are less frustrated by searching tasks than younger children.